Case report of a 19-year-old patient with β-thalassemia major, type 1 diabetes mellitus, osteoporosis and other major complications - Sohel Munaf, Momin; Mainoddin, Ariz Shaikh; Javeriya, Sana; Abid Asifali, Shaikh; Khan, Aasem; Shaikh, Juned (International Journal of Research in Medical Sciences, 2025)
This case report presents a detailed clinical profile of a 19-year-old male with β-thalassemia major, highlighting the multi-system complications associated with long-term disease management and chronic transfusion therapy. Diagnosed at one year of age due to symptoms including poor feeding, irritability, developmental delays, and failure to thrive, the patient’s haemoglobin electrophoresis showed markedly elevated HbF levels, confirming β-thalassemia major. Over the years, the patient has undergone regular transfusions and a splenectomy at age seven to address hypersplenism. Family screening in 2014 identified β-thalassemia trait in both parents and three siblings, prompting genetic counselling. In 2020, the patient developed diabetic ketoacidosis, presenting with hyperglycaemia and ketonuria, and was subsequently diagnosed with type 1 diabetes mellitus, managed with insulin therapy. By 2023, he exhibited signs of iron overload, with MRI showing iron deposition across multiple organs and serum ferritin levels exceeding 2000 ng/mL. Additional findings included hepatomegaly, mild pleural effusion, thyroid dysfunction, and osteoporosis confirmed by bone mineral density testing. Current management includes oral deferasirox for iron chelation, calcium and vitamin D supplementation, folic acid, and insulin therapy tailored to his glucose needs.